Cutaneous metastasis of transitional cell carcinoma of the urinary bladder: Cytological aspect - Modugumudi Ananta Satya Narayana; Rashmi Patnayak; Nandyala Rukmangadha; Amit Kumar Chowhan; Radhika Kottu; Bobbidi Venkatesh Phaneendra (Journal of Cytology, 2014)
Cutaneous metastasis from transitional cell carcinoma urinary bladder is a rare clinical entity associated with poor prognosis. This case report describes a 51-year-old male who presented with multiple cutaneous metastases arising from high grade transitional cell carcinoma bladder with lamina propria invasion. The prominent cytological features include medium sized to large pleomorphic cells with irregular nuclear outlines, coarse chromatin pattern, and tumor giant cells. An awareness of this rare clinical entity and high index of suspicion is needed for diagnosis.